PENGARUH LEVERAGE, EARNING POWER, DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA - Mishelei Loen, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The purpose of the reasearch to find out and analyze the effect of Leverage, Earning Power, and Managerial Ownership of Earnings Management, Study on Companies Conducting Right Issues on the Indonesia Stock Exchange for the period 2016-2020. The analytical method used in this study namely by using descriptive statistical methods and multiple regression then using classical assumption and hypothesis testing using T test, F test and R² test, sampling using purposive sampling method with a population of 55 from the population obtained 18 samples. The results showed that partially or according to the results of the T test, that Leverage, Earning Power, and Managerial Ownership have a significant effect on Study Management in Companies Conducting Right Issues on the Indonesia Stock Exchange for the 2016-2020 period.